Optimization of Green Extraction Methods and Characterization of Luteolin Particle Size from Celery (Apium graveolens) NaDES Ultrasonics for Drug Raw Material Independence - Rizky Yulion Putra; Ruri Putri Mariska; Putri Ningrum Nurin Latifah (Indonesian Scholar Society, 2026)
The development of luteolin extraction technology using NaDES (Natural Deep Eutectic Solvent) with celery (Apium graveolens) samples will result in technological advances in the self-sufficiency of medicinal raw materials derived from local natural resources. The objective of this research is to develop extraction method for luteolin compounds and to characterize the particle size nanoparticle extracts. Choline chloride is utilized as an HBA, lactic acid, glycerol, and glucose as HBDs. These substances are employed in combinations of 1:1, 1:3, and 1:5. Ultrasonic-assisted extraction (UAE) was performed with variations in time (15, 30, 60 minutes) and temperature (30, 50, 70°C). The %yield of luteolin compound was identified by UV-Vis spectrophotometer. Liquid chromatography-mass spectrometry (LC-MS/MS) was utilized to characterize each compound NaDES extract. Characterized particle size and zeta potental of each NaDES extract was using a particle size analyzer (PSA). The optimal %yield of 1.2468% was achieved through choline chloride-lactic acid (1:3) at 60 minutes and a temperature of 70°C. The characterization of luteolin 3'-methyl ether 7-malonylglucoside and luteolin 7-primeveroside compounds was successfully identified in apium graveolens NaDES extract. Characterization of the particle size and zeta potential values of each group of choline chloride–lactic acid, choline chloride–glycerol, and choline chloride–glucose were 292.2 nm, 428 nm, and 198.3 nm, respectively, with corresponding potential values of 167 mV, 133.9 mV, and 71 mV. Celery extract considerable potential for further development. Obtaining samples is a simple process, and the extract exhibits significant promise in supporting Indonesia's autonomy for domain of medicinal raw materials.